JmjC catalysed histone H2a N -methyl arginine demethylation and C4-arginine hydroxylation reveals importance of sequence-reactivity relationships - Bonnici, J; Oueini, R; Salah, E; Johansson, C; Pires, E; Abboud, M; Dawber, RS; Tumber, A; Rabe, P; Saraç, H; Schofield, CJ; Kawamura, A (Nature Research, 2024)
2-Oxoglutarate (2OG) dependent Nε-methyl lysine demethylases (JmjC-KDMs) regulate eukaryotic transcription. We report studies showing that isolated forms of all human KDM4 and KDM5 JmjC enzymes catalyse demethylation of N-methylated Arg-3 of histone H2a. Unexpectedly, the results reveal that KDM4E and, less efficiently, KDM4D catalyse C-4 hydroxylation of Arg-20 of H2a on peptides, recombinant H2a, and calf histone extracts, including when the Arg-20 guanidino group is N-methylated. Combined with previous observations, our biochemical results highlight the importance of sequence context in determining the relative efficiencies of lysine and arginine demethylation reactions catalysed by KDM4s and KDM5s. At least in some cases changes in sequence can also enable a different JmjC reaction mode, such as C-4 arginine hydroxylation instead of demethylation. Further work is thus required to define the full scope of JmjC catalysed reactions in cells.